Depression is associated with increased disease activity in patients with ulcerative colitis: A propensity score‐matched analysis using a nationwide database in Japan. Issue 12 (15th November 2022) - Oyama, Hideaki; Moroi, Rintaro; Tarasawa, Kunio; Shimoyama, Yusuke; Naito, Takeo; Sakuma, Atsushi; Shiga, Hisashi; Kakuta, Yoichi; Fushimi, Kiyohide; Fujimori, Kenji; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Background and Aim: The incidence and prevalence of psychiatric disorders are elevated in patients with inflammatory bowel disease (IBD). Whether psychiatric disorders could affect the clinical course of IBD is uncertain and controversial. We aimed to evaluate the impact of psychiatric disorders, particularly depression, on the clinical course of IBD using a nationwide database in Japan. Methods: We collected data on admissions with IBD using the Diagnosis Procedure Combination database system introduced in Japan. We divided eligible admissions into IBD with and without depression groups using propensity score matching and compared the rates of surgery, use of molecular targeted drugs and biologics, systemic steroid administrations, and in‐hospital death. We also conducted a logistic regression analysis to identify clinical factors affecting surgery, the use of molecular targeted drugs and biologics, and systemic steroid administrations. Results: The rates of surgery, use of two or more molecular targeted drugs, systemic steroid administrations, and in‐hospital deaths in the ulcerative colitis (UC) with depression group were higher than in the UC without depression group. Multivariate analysis of UC showed that depression increased the odds of systemic steroid administrations, use of two or more molecular targeted drugs, and surgery. However, analysis of Crohn's disease showed that only steroid administrations were associated with depression. Conclusion: Our study demonstrated an association between a worse clinical course of UC and depression. Although this result indicates that depression might be associated with increased disease activity in patients with UC, the causal relationship is still unclear. Further prospective studies are warranted. Abstract : Depression might be associated with increased disease activity in patients with ulcerative colitis (UC), which could lead to a poor clinical course. It might be better to consider referring patients with UC who have depressive symptoms to a psychiatrist to improve their clinical course.